HUBUNGAN ANTARA TINGKAT OBESITAS DENGAN KONSEP DIRI PADA REMAJA PUTRI DI KEDUNGGUPIT SIDOHARJO WONOGIRI - Sri Yulianti, Tunjung; -, Dinar Ariasti (Intan Husada : Jurnal Ilmiah Keperawatan, 2015)
Introduction: This study is the estimate of WHO as many as 315 million people worldwide are categorized as obese with  more  women than  men. Among  adolescent  obesity  is  a  worrying  problem,  obtained  the  condition of  the  majority  of  young  women  who  are  overweight  (obese)  with confidence is lackingPurpose of the study: is to determine the number of young women who are  obese,  and  the  concept  of  self-possessed  young  women  who  are overweight  or  obese  can  be  called,  as  well  as  to  determine  the relationship between self-concept levels of obesity in adolescent girls. Subjects: of  this  study  were  all  obese  young  women  between  14-22 years of age.Methode  : This  research  method  using  cross  sectional  approach  The study  was  conducted  by  measuring  the  weight  and  giving  questioner  to the teenagers who had weight included in obesity. This data was analyzed using chi square.Results: showed  the  average  self-concept  is  owned  by  teenagers  who are  obese  is  a  negative  self-concept,  with  the  data  processing  SPSS value of p = 0.014, which means the value of p <0.05 so ha ho accepted and  rejected,  then  there  is  a  relationship  between  the  degree  of  obesity with the concept of self in adolescent girls.Conclusion : there  is  a  relationship  between  the  level  of  obesity  in  the young women's self-concept Kedunggupit Sidoharjo Wonogiri.Keywords: obesity rates, self-concept